2018
DOI: 10.1093/ndt/gfy204
|View full text |Cite
|
Sign up to set email alerts
|

Regional variation in the treatment and prevention of peritoneal dialysis-related infections in the Peritoneal Dialysis Outcomes and Practice Patterns Study

Abstract: Variation in PD-related infection prevention and treatment strategies exist across countries with limited uptake of ISPD guideline recommendations. Further work will aim to understand the impact these differences have on the wide variation in infection risk between facilities and other clinically relevant PD outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
71
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 67 publications
(77 citation statements)
references
References 39 publications
3
71
1
2
Order By: Relevance
“…It has also been demonstrated that in many countries it is very common not to follow these ISPD recommendations. 15 The fact that many patients discontinued the study, mainly due to kidney transplantation, transfer to hemodialysis, and death, could have altered the probability of a first peritonitis episode over the course of the study. We therefore used the Fine and Gray analysis to take these competing risks into account, as has been recommended for survival analysis in PD research.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been demonstrated that in many countries it is very common not to follow these ISPD recommendations. 15 The fact that many patients discontinued the study, mainly due to kidney transplantation, transfer to hemodialysis, and death, could have altered the probability of a first peritonitis episode over the course of the study. We therefore used the Fine and Gray analysis to take these competing risks into account, as has been recommended for survival analysis in PD research.…”
Section: Discussionmentioning
confidence: 99%
“…Although the recommendations state that the overall peritonitis rate should be below 0.5 episodes per patient-year, there is a wide variation in the peritonitis rates reported by different countries, as well as by different centers within the same country (8). A recent study shows highly variable rates of adopting the ISPD recommendations across different centers, and such variations probably account for the difference in infection risk between PD centers (9).…”
Section: Reporting Of Peritonitis Ratementioning
confidence: 99%
“…In Australia and New Zealand, for instance, 89% of the centers used antifungal prophylaxis compared with 54% in the United States and only 8% in Japan. 6 Of note, consideration for fungal prophylaxis practice needs to be taken in the context of individual countries and centers because the utility of this approach might be lower in centers with low rates of fungal peritonitis. The preferred agent in our opinion is nystatin, given the low cost and safety profile with a dose of 500,000 units orally 4 times per day for the entire duration of antibiotic therapy plus 1 week.…”
Section: We Do Not Consider Antifungal Prophylaxismentioning
confidence: 99%